The Metastability and Nucleation Thresholds of Ibuprofen in Ethanol and Water-Ethanol Mixtures - Abdur Rashid; Edward T. White; Tony Howes; James D. Litster; Ivan Marziano (International Journal of Chemical Engineering)
To investigate the crystallization of ibuprofen [((RS)-2-(4-(2-methylpropyl) phenyl) propanoic acid)] from ethanol and water-ethanol mixtures it is necessary to know the nucleation limits of its solutions. In the absence of crystals, nucleation will seldom occur below the PNT (primary nucleation threshold). If crystals are present, nucleation will seldom occur until below the lower SNT (secondary nucleation threshold). Below the SNT, crystals will still grow with negligible nucleation. PNT and SNT values (expressed as relative supersaturation σ) have been measured at 10, 25, and 40°C for ibuprofen in ethanol and in a range of mixtures of different ethanol (E)/water (W) ratios. The induction times were determined from observing the times to nucleate for a range of different supersaturated solutions at a given temperature and E/W ratio. As expected, lowering the supersaturation leads to longer induction times. In ethanol, the SNT values are small and thus the secondary metastable zone width (MSZW) is relatively narrow with a 1 h SNT relative supersaturation typically about σ ~ 0.05. The 1 h PNT values are much larger with values for σ around 0.3. In aqueous ethanolic mixtures at 25°C, both the PNT and SNT decrease as the water content increases.